Glomerulogenesis: Can it predict the gestational age? A study of 176 fetuses - Panduranga Chikkannaiah; Maitrayee Roy; Ranjit Kangle; Prakash V Patil (Wolters Kluwer Medknow Publications, 2012)
Background: Accurate assessment of gestational age of fetuses is essential from both clinical and medico-legal point of view. Crown-rump length, crown-heel length, foot length, and the weight of the fetus are the commonly used parameters for fetal age assessment. However, this estimate often lacks accuracy and sometimes is necessary to combine other data. An analysis of the embryological development of nephrons in the kidney can assist in this determination. Objective : To correlate the gestational age with the histological study of sequential development of nephrons in fetal kidney. Materials and Methods: This study included 176 fetuses delivered between June 2009 and June 2011 and aged from 12 to 40 weeks. The number of glomerular generations counted in hematoxylin and eosin-stained microscopic sections of the kidneys were correlated with the reported period of gestation based on obstetrical methods. Regression analysis was used to determine the statistical significance of the correlation. Results: A high degree of statistically significant correlation was observed between the period of gestation and the number of glomerular generations (P value < 0.0001). Conclusion: The histological assessment of the number of glomerular generations in kidney can be used as a reliable method of estimating fetal age.